Secondary School Teachers’ Perception of Leadership Competencies of Headteachers who were Forcibly Transferred from their Previous Schools - Martin Muyingo (International Journal of Natural Sciences: Current and Future Research Trends, 2024)
The study sought to explore teachers’ perception of Leadership competences of forcibly transferred head teachers in the Government aided secondary schools in the central Region of Uganda. This study was based on a phenomenological design where the study participants involved teachers, headteachers and commissioner secondary education and human resource departments of MoES. These participants were purposively selected. Actual number of participants depended on saturation of result Interview guides were the data collection instruments. This data was analyzed using thematic data analysis technique. Results also revealed that headteachers without leadership competencies like initiative self-confidence, who were not accountable, transparent, lacked emotional control among others used to be transferred using forced transfer means. Hence, the study concluded; that headteachers without with leadership competencies (self-awareness, emotional control, transparency, accountability, achieving highly, having high confidence) among others were transferred using by force. The study therefore recommends that relevant stakeholders at MoES, Department of Secondary School Education, Board of Governors to do the following to improve on headteachers transfers: There is need to emphasize the headteachers to reflect on the leadership competencies desired in the current age. This would be done by; Organizing refresher training courses like workshops, study conferences, study leaves to ensure that these headteachers develop desired leadership competencies at school. Secondly there is also need to inform and alert headteachers of leadership incompetencies that could lead to forced transfer from school.